2020
DOI: 10.1016/j.msard.2020.102282
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 prevention and multiple sclerosis management: The SAFE pathway for the post-peak

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…One group has proposed the SAFE protocol based on the Italian experience during COVID-19. This includes standardizing protocols for Screening [for COVID-19 associated symptoms], Access [to MS care], Face [coverings] and E-health [options for MS] ( Bunonomo et al., 2020 ). A “massive investment” for dedicated resources and human and technological services has been called for in the case of neurorehabilition in particular, even while recognizing that remote evaluations have clear limitations ( Leocani et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…One group has proposed the SAFE protocol based on the Italian experience during COVID-19. This includes standardizing protocols for Screening [for COVID-19 associated symptoms], Access [to MS care], Face [coverings] and E-health [options for MS] ( Bunonomo et al., 2020 ). A “massive investment” for dedicated resources and human and technological services has been called for in the case of neurorehabilition in particular, even while recognizing that remote evaluations have clear limitations ( Leocani et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is currently unknown whether lymphopenia represents a risk factor for morbidity and mortality from COVID-19, or is actually beneficial by preventing the abnormal systemic immune response ( Parrotta et al., 2020 , Minotti et al., 2020 ). We have shown that MS patients with lymphopenia following cladribine treatment can develop mild or no symptoms from COVID-19, suggesting that lymphopenia is not necessarily a risk factor for worse disease outcomes, and immunosuppressive DMTs do not necessarily need to be suspended or delayed in the course of the current pandemic ( Giovannoni et al., 2020 , Buonomo et al., 2020 ). This consideration applies to both a young, newly-diagnosed, drug-naïve patient and to an adult patient with comorbidities and long standing history of MS clinical features and treatments.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that the generalizability of our considerations is limited, deriving from the observation of two isolated cases, but we believe that they represent valuable hints needing confirmation in larger populations. Also, while COVID-19 testing for all MS patients dosing/redosing immunosuppressive DMTs has been suggested ( Buonomo et al., 2020 ), there are differences between healthcare systems and local protocols that should be accounted for when translating our considerations in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, people with MS have higher prevalence of a number of comorbidities (e.g., cardiovascular) when compared with the general population [ 3 , 4 ]. Not least, the use disease-modifying treatments (DMTs), causing different degrees of systemic immunosuppression, might further affect the possibility of preventing and responding to the infection [ 5 ]. In line with this, healthcare providers and policy makers have immediately advised people with MS to self-isolate, and the use of immunomodulatory and immunosuppressive DMTs has been postponed [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%